Biodiversity of Social Wasps (Hymenoptera: Vespidae) at Altitudes Above 1600 Meters in the Parque Estadual da Serra do Papagaio, State of Minas Gerais, Brazil - Souza, Marcos Magalhães de; Silva, Heloina Nathalliê Mariano da; Dallo, João Batista; Martins, Lizandra de Fátima; Milani, Lucas Rocha; Clemente, Mateus Aparecido (EntomoBrasilis, 2015)
The Parque Estadual da Serra do Papagaio is the largest area of natural preservation in the south of Minas Gerais, with areas of Floresta Atlantica, Floresta de Araucaria and Campos de Altitude. Although this is an area of biological importance, there are many groups that have not yet been studied there: for example social wasps, which are insects belonging to order Hymenoptera, family Vespidae, which play an important ecological role in different ecosystems. This study was carried out in the aforementioned natural preservation area at altitudes between 1600 and 2200 m in 20 days of sampling between July of 2013 and April of 2014, using active searches and attractive traps to record species. Twenty two species of social wasps were sampled, distributed in seven genera. This number is small compared to counts from other studies in this state, which is probably due to the high altitude of this area. There was a predominance of nests with protective casings in the most common species recorded, and the most populous species was Polybia fastidiosuscula Saussure, a finding that can be explained by the superior thermoregulation afforded by the nest casing. Two other common species were Mischocyttarus drewseni Saussure, and Mischocyttarus rotundicolis (Cameron), which have nests without casings; however, these species have dark coloration, as does the substrate used for nesting, and can therefore enhance retention of solar radiation; nevertheless, other biotic and abiotic factors could be involved. Biodiversidade de Vespas Sociais (Hymenoptera: Vespidae) em Áreas de Altitude Acima de 1600 Metros do Parque Estadual da Serra do Papagaio, Estado de Minas Gerais, Brasil Resumo. O Parque Estadual da Serra do Papagaio é a maior Unidade de Conservação do sul de Minas Gerais, com áreas de Mata Atlântica, floresta de Araucária e Campos de Altitude. Apesar da importância biológica da área, muitos grupos animais não foram estudados, como as vespas sociais, insetos que pertencem à ordem Hymenoptera, família Vespidae, e que desempenham importante papel ecológico em diferentes ecossistemas. O estudo foi conduzido nessa Unidade de Conservação em altitudes entre 1600 a 2200 m, no período de julho de 2013 a abril de 2014, durante vinte dias de amostragem, utilizando busca ativa e armadilhas atrativas para registro das espécies. Foram amostradas 22 espécies de vespas sociais distribuídas em sete gêneros. Número menor em relação a outros estudos do estado, o que, provavelmente, foi ocasionado pela elevada altitude. Houve uma predominância de ninhos com invólucro protetor e a espécie mais frequente foi Polybia fastidiosuscula Saussure, o que pode ser explicado pela melhor regulação térmica obtida pelo invólucro. Outras duas espécies frequentes foram Mischocyttarus drewseni Saussure e Mischocyttarus rotundicolis (Cameron) que possuem ninhos sem invólucro, porém essas espécies possuem coloração escura, assim como o substrato utilizado para nidificação e isso poderia reter melhor a radiação solar. Contudo outros fatores bióticos e abióticos podem estar envolvidos.